Robotic process automation and reengineering using Bizagi and UiPath: case study on mortgage request process. (23rd March 2022) - Aljuhani, Nouf; Alshahrani, Fatimah; Alharbi, Amani; Aldini, Nuha; Albalawi, Hawazin; Elhag, Salma
Recently, robotic process automation (RPA) has become increasingly adopted by different institutions in an endeavour to improve business performance. However, banking and financial institutions are still considered a slow-developing sector lacking sufficient experience with different aspects of process automation. Therefore, the main aim of this work is to examine how RPA adoption can affect the performance of banking processes by conducting a case study on the mortgage loan application process of a bank located in Saudi Arabia. A well-established methodology inspired by the business process management (BPM) lifecycle has been followed. We utilise the Bizagi (BPM) Suite to model and analyse AS-IS and TO-BE scenarios of the process. UiPath software has been used to build and configure the RPA bot. The simulation results revealed that the adoption of the RPA within the mortgage loan application process has reduced the overall cycle time of the process by approximately 14 days.